Safety Profile of Kumarkalyan Rasa: Subchronic Toxicity Study in Wistar Rats - Pawar, Shubhangi; Mohan, Mahalaxmi; Ohol, Uttarksha; Pande, Shishir; Kulkarni, Rajshree; Kulkarni, Abhay (Asian Journal of Biological and Life Sciences, 2025)
Kumarkalyan Rasa (KR), a proprietary herbometallic medicine, is used in children to treat a variety of health issues. Because it contains heavy metals, concerns have been raised about the safety of ayurvedic medicines containing heavy metals. Goal of current work was to conduct the subchronic toxicity of KR after prolonged intake. The experimental animals were divided into four groups (n=6). Three groups received oral KR suspension at dosages of 51.36, 205.44, and 513.6 mg/kg for 90 days. The vehicle treated group served as control. All of the animals were evaluated for evidence of mortality and toxicity. Over the dosage period, all treated and control group animals gained weight and gradually increased their feed consumption and water intake. But results revealed no significant difference in treated animals and control animals. Urine samples were collected 1 week before scarification for analysis. On day 91, after scarification, haematological and biochemical parameters for the treated and control animals were estimated. Treatment with KR had no effect on urine, haematological and biochemical parameters in comparison with control animals. The safety of KR administration is also supported by histopathological examination which has not shown any abnormal changes in any of the vital organs. Thus, Kumarkalyan Rasa is concluded as a safer therapeutic approach and can be used clinically.
Keywords: Ayurveda; Herbometallic; Kumarkalyanrasa; Subchronic oral toxicity